Advanced nanostructured medical device combining mesenchymal cells and VEGF nanoparticles for enhanced engineered tissue vascularization. (September 2016) - Wagner, Quentin; Offner, Damien; Idoux-Gillet, Ysia; Saleem, Imran; Somavarapu, Satyanarayana; Schwinté, Pascale; Benkirane-Jessel, Nadia; Keller, Laetitia
Aim: Success of functional vascularized tissue repair depends on vascular support system supply and still remains challenging. Our objective was to develop a nanoactive implant enhancing endothelial cell activity, particularly for bone tissue engineering in the regenerative medicine field.Materials & methods: We developed a new strategy of tridimensional implant based on cell-dependent sustained release of VEGF nanoparticles. These nanoparticles were homogeneously distributed within nanoreservoirs onto the porous scaffold, with quicker reorganization of endothelial cells. Moreover, the activity of this active smart implant on cells was also modulated by addition of osteoblastic cells.Results & conclusion: This sophisticated active strategy should potentiate efficiency of current therapeutic implants for bone repair, avoiding the need for bone substitutes.